Atypical Self-Focus Effect on Interoceptive Accuracy in Anorexia Nervosa - Pollatos, Olga; Herbert, Beate M.; Berberich, Götz; Zaudig, Michael; Krauseneck, Till; Tsakiris, Manos (Frontiers in Human Neuroscience, 2016)
Background: Interoceptive abilities are known to be affected in anorexia nervosa (AN). Previous studies could show that private self-focus can enhance interoceptive accuracy (IAcc) in healthy participants. As body dissatisfaction is high in AN, confrontation with bodily features such as the own face might have a directly opposed effect in AN. Whether patients with AN can benefit from self-focus in their IAcc and whether this pattern changes over the time-course of cognitive behavioral therapy was investigated in this study. Methods: 15 patients with AN from the Psychosomatic Clinic in Windach were assessed three times in the time course of a standardized cognitive-behavioral therapy. They were compared to 15 controls, recruited from Ulm University and tested in a comparable setting. Both groups performed the heartbeat perception task assessing interoceptive accuracy (IAcc) under two conditions either enhancing (“Self”) or decreasing (“Other”) self-focused attention. Furthermore, body dissatisfaction was assessed by a subscale of the Eating Disorder Inventory 2. Results: Patients with AN scored higher in IAcc when watching others’ faces as compared to one’s own face while performing the heartbeat perception task. The opposite pattern was observed in controls. IAcc remained reduced in AN as compared to controls in the time-course of cognitive-behavioral therapy, while body-dissatisfaction improved in AN. High body dissatisfaction was related to poorer IAcc in the “Self” condition. Conclusions: Our findings suggest that using self-focused attention reduces IAcc in AN while the opposite pattern was observed in controls. Confronting anorexic patients with bodily features might increase body-related avoidance and therefore decrease interoceptive accuracy. The current study introduces a new perspective concerning the role of interoceptive processes in AN and generates further questions regarding the therapeutic utility of methods targeting self-focus in the treatment of AN.